Форми інфраструктури - Яковенко, Р. В.; Yakovenko, R. (My University, 2018)
Наведено різні форми інфраструктури, структуру інфраструктури ринку засобів виробництва. Different forms of infrastructure, structure of infrastructure of the market of means of production are presented.
Infrastructure forms
Keywords: форми інфраструктури; інжиніринг; спеціалізована ринкова інфраструктура; infrastructure forms; engineering; specialized market infrastructure